Individual and organizational predictors of allied healthcare providers' job satisfaction in residential long-term care - Laura D. Aloisio; Wendy A. Gifford; Katherine S. McGilton; Michelle Lalonde; Carole A. Estabrooks; Janet E. Squires (BMC, 2018)
Abstract Background Job satisfaction is a predictor of intention to stay and turnover among allied healthcare providers. However, there is limited research examining job satisfaction among allied health professionals, specifically in residential long-term care (LTC) settings. The purpose of this study was to identify factors (demographic, individual, and organizational) that predict job satisfaction among allied healthcare providers in residential LTC. Methods We conducted a secondary analysis of data from Phase 2 of the Translating Research in Elder Care program. A total of 334 allied healthcare providers from 77 residential LTC in three Western Canadian provinces were included in the analysis. Generalized estimating equation modeling was used to assess demographics, individual, and organizational context predictors of allied healthcare providers' job satisfaction. We measured job satisfaction using the Michigan Organizational Assessment Questionnaire Job Satisfaction Subscale. Results Both individual and organizational context variables predicted job satisfaction among allied healthcare providers employed in LTC. Demographic variables did not predict job satisfaction. At the individual level, burnout (cynicism) (β = −.113, p = .001) and the competence subscale of psychological empowerment (β = −.224, p = < .001), were predictive of lower job satisfaction levels while higher scores on the meaning (β = .232, p = .001), self-determination (β = .128, p = .005), and impact (β = .10, p = .014) subscales of psychological empowerment predicted higher job satisfaction. Organizational context variables that predicted job satisfaction included: social capital (β = .158, p = .012), organizational slack-time (β = .096, p = .029), and adequate orientation (β = .088, p = .005). Conclusions This study suggests that individual allied healthcare provider and organizational context features are both predictive of allied healthcare provider job satisfaction in residential LTC settings. Unlike demographics and structural characteristics of LTC facilities, all variables identified as important to allied healthcare providers' job satisfaction in this study are potentially modifiable, and therefore amenable to intervention.